Kultura organizacyjna jako czynnik wpływający na funkcjonowanie przedsiębiorstwa: Organizational culture as a factor affecting the functioning of the company - Szmurło, Agnieszka (Management and Administration Journal, 2021)
Organizational culture is one of the main factors affecting the operation of the organization. You can go so far as to say that the value of the company is dependent on the culture,because significantly effect on the behavior and attitudes of employees, also is a factor affectingthe implementation of the strategy and supporting the operation of the company. Organizationalculture is the result of relationships: supervisor - subordinate, employer - employer (at the samelevel), the company - the environment. It is important to build a culture that will effectively support the company's competitiveness in the market. The purpose of this article is to show howorganizational culture affects the functioning of the company.